(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Evaluation of lower wisdom teeth surgery results at Thai Binh Medical University Hospital. Subjects and methods: Progressive study on 143 subjects with lower wisdom teeth surgery at Thai Binh Medical University Hospital from November 2019 to June 2020. Results: Parant type II surgery accounted for the highest rate 44.76%. Surgery time from 30-60 minutes accounts for the majority of 48.25%. In the process of surgery, the most common accident is fracture/rupture of the bone in the lower wisdom teeth accounting for 57.34%, root fracture accounts for 11.89%, a case of mild late anesthetic allergy is recorded. Long-term bleeding complications accounted for 11.19%; dry alveolar acupressure and wet alveolar acupressure accounted for 8.39% and 7.69% respectively. Conclusions: According to Parant dividing lower wisdom teeth surgery into 4 types, the rate of type II surgery, ie tooth extraction needs to open a part of the alveolar bone and cut the neck of the teeth for the majority.